Design of Solar Powered Subscale Glider for CanSat Competition - Aliyev, Ilkin; Misirli, Cahit Abdullah; Ozturk, Selim; Mahmurat, Emrullah; Erkek, Abdussamet; Kok, Selahattin; Kocyigit, Davut; Uzun, Sukru; Vural, Revna Acar (IEEE, 2017)
This paper briefly describes glider designed by IQRASAT Team from Yildiz Technical University for CanSat Competition 2017. CanSat competition is a design-build-launch competition that provide teams with hand on experience. The paper mainly focuses on the design of an innovative science glider. Hardware and software subsystem of CanSat is presented in detail as well as ground station for telemetry reception. The design procedure is described with the preliminarily designed complete system satisfies the rules of CanSat 2017
Keywords: Model Satellite; Deltawing Glider; Energy Harvester; CanSat; CanSat2017; Engineering; Remote Sensing